Effect of carbohydrate or sodium bicarbonate ingestion on performance during a validated basketball simulation test - Afman, G.; Garside, R. M.; Dinan, N.; Gant, N.; Betts, J. A.; Williams, C. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
Current recommendations for nutritional interventions in basketball are largely extrapolated from laboratory-based studies that are not sport-specific. We therefore adapted and validated a basketball simulation test relative to competitive basketball games using well-trained basketball players (n = 10), then employed this test to evaluate the effects of two common preexercise nutritional interventions on basketball-specific physical and skilled performance. Specifically, in a randomized and counterbalanced order, participants ingested solutions providing either 75 g carbohydrate (sucrose) 45 min before exercise (Study A; n = 10) or 2 × 0.2 g·kg-1 sodium bicarbonate (NaHCO3) 90 and 20 min before exercise (Study B; n = 7), each relative to appropriate placebos (H2O and 2 × 0.14 g·kg-1 NaCl, respectively). Heart rate, sweat rate, pedometer count, and perceived exertion did not systematically differ between the 60-min basketball simulation test and competitive basketball, with a strong positive correlation in heart rate response (r = .9, p < .001). Preexercise carbohydrate ingestion resulted in marked hypoglycemia (< 3.5 mmol·l-1) throughout the first quarter, coincident with impaired sprinting (+0.08 ± 0.05 second; p = .01) and layup shooting performance (8.5/11 versus 10.3/11 baskets; p < .01). However, ingestion of either carbohydrate or sodium bicarbonate before exercise offset fatigue such that sprinting performance was maintained into the final quarter relative to placebo (Study A: -0.07 ± 0.04 second; p < .01 and Study B: -0.08 ± 0.05 second; p = .02), although neither translated into improved skilled (layup shooting) performance. This basketball simulation test provides a valid reflection of physiological demands in competitive basketball and is sufficiently sensitive to detect meaningful changes in physical and skilled performance. While there are benefits of preexercise carbohydrate or sodium bicarbonate ingestion, these should be balanced against potential negative side effects.